Commands in Deni (Arawá) - Carvalho, Mateus Cruz Maciel de (2016)
All languages provide to its speakers mechanisms for expressing a command. The way in which languages express commands is, however, different. This paper focus on Deni, an Arawá languages spoken in southern Amazon – Amazonas state, Brazil – by about 1,500 people who live in nine villages, six on the Cuniuá river and three on the Xeruã river. Deni has basically two ways for making a command: (i) morphologically, attaching a imperative morpheme to a verb root; and (ii) lexically, by suppletive forms and manner adverbs. The four imperative morphemes identified in the database are divided into canonical imperatives, which are only directed to the second person, and non-canonical imperatives, which are directed to first person. Whereas canonical imperatives can be negated, non-canonical imperatives only have the positive form. Furthermore, imperatives are used under cultural constrains, given that the non-polite imperative is a rude way of making and command and, hence, has a limited usage according with people involved in the conversation. Suppletive forms are used in a different way when compared to verbs. They are mostly used by themselves along with gestures and are quite different from verbs – whilst verbs have a very rich morphology, suppletive forms do not take any morpheme. Manner adverbs have also been attested in command constructions. They are used for making a command in relation to an activity which has already begun.